Portuguese as a heritage language in contact with German and French: a comparative study on the acquisition of verbal mood - Flores, Cristina (2019)
This study focuses on the acquisition of verbal mood in complement clauses by two groups of heritage speakers of European Portuguese (EP) (7–16 years old) with similar sociolinguistic profiles and two different dominant languages, German and French. The production of finite complement clauses was elicited through a sentence completion task. By comparing two bilingual groups with different dominant languages (a Romance language with a subjunctive mood encoding the same semantic values as EP and a Germanic language with no similar linguistic category), we discuss the relative weight of cross-linguistic influence and of amount of exposure in bilingual acquisition. The results show protracted development of both bilingual groups concerning the subjunctive, with no negative effect observed in the bilingual speakers who are dominant in German. We conclude that cross-linguistic influence cannot explain this performance and suggest that amount of input plays a role.